Perbedaan Metoda Penyuluhan dengan Menggunakan Leaflet dan Video dalam Merubah Pengetahuan Sikap dan Perilaku Siswa SD Mengenai Pemilihan Makanan Jajanan - Wiwit Handayani; Narto Narto; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2015)
Snacks can not be separable from elementary school children’ daily activities. But, they have to be more selective in choosing the foods because some studies revealed that some dangerous substances were contained. The aim of the study was to know whether leaflet and video used in elucidation have difference effects towards the knowledge, attitudes and behavior of students of Pujokusuman 1 Elementary School of Yogyakarta City in selecting snacks. The type of this research was an experiment following pre test post test with control group design. As the respondents were 169 grade 4 and 5 students who were divided into three groups, i.e. 57 studentswere assigned to group of leaflet media, another 57 students were assigned to group of video media, and the rest 56 students were assigned to the control group. Students of grade 4 and 5 were chosen as the study sample because they are assumed already had good reading and writing skills as well as can receive information properly. The data obtained were examined by using independent t-test at significance level (?) 0,05 because the assumption of distribution normality was met. The p-values gained from the the test were less than 0,001 for all tests, so that it can be interpreted that leaflet and video used in the elucidation, improved students’ knowledge, attitude and practice. Since video was also found give better results compared with the leaflet did, the stakeholders are advised to implement this media as one of alternative methods in delivering information, in order to make the students can choose the healthy snacks.